Trends in Exposure to Televised Prescription Drug Advertising, 2003–2011 - Kornfield, Rachel (Am J Prev Med, 2015)
INTRODUCTION: TV accounts for over half of pharmaceutical direct-to-consumer advertising (DTCA) spending in the U.S. The purpose of this study is to quantify average household exposure to branded and non-branded (help-seeking) televised prescription drug advertisements and describe variation over time and according to medication indication and geography. METHODS: In 2013, Nielsen TV ratings were compiled for prescription pharmaceutical advertising that aired between 2003 and 2011 for the top 75 U.S. media markets. All advertisements were coded as branded or help-seeking. Advertisements were further coded for one of eight prevalent indications (allergies, arthritis, asthma, erectile dysfunction, high cholesterol, smoking cessation, depression, and sleep disorder) or as “other.” RESULTS: Televised DTCA exposure increased from 2003 to 2007 and then declined 43% by 2011, to 111 monthly prescription drug advertisements per household. The examined indications were associated with varying amounts and patterns of exposure, with greatest declines among medications for allergies and sleep disorders. Help-seeking advertisements comprised 10% of total exposure, with substantial variation by indication. CONCLUSIONS: Considerations of DTCA's effects on health care should take into account the shifting concentration of advertising across indications.